Supersonic wind-tunnel : nozzle design and control system analysis - Cox, Riordan Howard Tesling (Department of Mechanical Engineering, 2016)
Symmetrical two-dimensional nozzles were designed for the supersonic wind-tunnel, in the Department of Mechanical Engineering, using both analytical and semigraphical methods obtained from the theory of Characteristics. These nozzles, designed for an optimum running time of 30 seconds, at a Mach number of 2,35. Boundary layer growth was considered by displacing the nozzle contours outwards by the equivalent displacement thickness, while keeping the vertical tunnel side walls parallel. The five pitot probe calibration results, taken through the central vertical plane in the tunnel test-section, showed Mach number standard deviations about the mean of 0,638% and 1,004% for the analytical and semi-graphical design respectively. These results compare ·very favourably with those of other wind- tunnels. Without pressure recovery the critical flow pressure ratio through the tunnel for Mach 2,35 nozzles, is 2,53. Therefore it may be shown that the subsonic diffuser, and the silencer incorporated into it, is about 75% efficient. The analysis and modification to the existing settling chamber control valve yielded improvements in performance. 1. The maximum fluctuation in settling chamber pressure was kept to within 5,5% for most operating conditions. 2. Critical valve response was achieved by applying a suitable bypass orifice to the damping cylinder - The valve settled down within one second after flow had been initiated. A proposed variable symmetrical nozzle was examined for the feasibility of its application to the existing supersonic wind-tunnel.